A Disease in Disguise-A Case Report on an Atypical Presentation of Bowen's disease - Raj Kirit, E.P; Saketha , Ananthula; Attili, Sasi Kiran; Ponugupati , Sridevi (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Bowen’s disease (BD) is a rare premalignant condition. The etiology of Bowen’s disease is multifactorial. Classically, it presents as a well‑demarcated erythematous plaque, predominantly in photo-exposed areas. The morphology of Bowen’s disease differs based on the age of the lesion, the site of origin, and the degree of keratinization. Atypical variants in terms of morphology, such as verrucous, hyperkeratotic, atrophic, and pigmented types, are rarely described in the literature. Bowen’s disease can be a diagnostic challenge for a physician as it mimics common conditions such as psoriasis, eczema, warts, etc. Histopathology is the gold standard diagnostic modality for confirming the diagnosis. The treatment depends on site, size, immune status, patient’s age, aesthetic outcome, etc. The available therapeutic modalities include topical chemotherapy, surgical treatments, and light-based therapies. Here, we present a case report of an atypical presentation of Bowen’s disease. A 68-year-old male came to the clinic with complaints of a raised skin-coloured lesion over his right ear for 45 days. On examination, a solitary, well-defined skin coloured – slightly yellow-coloured verrucous papule was seen over the helix of the right ear. A differential diagnosis of verruca vulgaris, Bowen’s disease, and Bowenoid papulosis was made and sent for histopathology. Histopathological findings were consistent with Bowen’s disease.